2010
DOI: 10.1136/adc.2009.176925
|View full text |Cite
|
Sign up to set email alerts
|

The fifth UK paediatric diabetes services survey: meeting guidelines and recommendations?

Abstract: Paediatric and adolescent diabetes services are rising to the challenge of providing high-quality care despite rising prevalence and increasingly complex insulin regimes. Services have improved in a number of key areas but serious deficiencies remain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 6 publications
1
41
0
Order By: Relevance
“…While rosiglitazone appeared most effective in the adolescents in TODAY, in adults, the use of agents in the thiazolidinedione class has now declined due to cardiovascular and bone density safety concerns 64,65 . However, serious adverse events did not differ between arms in TODAY.…”
Section: Maahs Et Al Cvd Risk Factors In Youth With Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…While rosiglitazone appeared most effective in the adolescents in TODAY, in adults, the use of agents in the thiazolidinedione class has now declined due to cardiovascular and bone density safety concerns 64,65 . However, serious adverse events did not differ between arms in TODAY.…”
Section: Maahs Et Al Cvd Risk Factors In Youth With Diabetes Mellitusmentioning
confidence: 99%
“…62 A study in the United Kingdom found 83.5% compliance with lipid screening with T1DM, 63 and another in children with T2DM found that only half of the patients had lipid testing. 64 In a survey by Gosden et al, 65 only 66% of patients had their BP checked yearly, and other CVD risk factors were not addressed. The SEARCH study reported self-assessed adherence to guidelines in 1514 participants.…”
Section: Overview Of Current Guidelinesmentioning
confidence: 99%
“…This rate is lower than that reported for 2008 for the United Kingdom, 44%. 13 Although we report availability of funded 24-hour support for patients using pumps, our clinical experience suggests that centres that provide this service are likely to do so for all patients regardless of their insulin regimen.…”
Section: Discussionmentioning
confidence: 88%
“…14 In the United Kingdom in 2008, 94% of centres had a diabetes specialist nurse, 88% of whom worked solely in pediatrics. 13 In the European study, the number of patients per nurse ranged from 140 to 184 across centre size, 14 and in the UK study, the median was 92, 13 considerably lower than that in the Ontario network. In the UK, 93% of clinics reported having a pediatric dietitian, and only 21% had a psychologist.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation